Mobile medical app development with a focus on traceability. Issue 11 (17th March 2017) - Trektere, Kitija; Regan, Gilbert; Caffery, Fergal Mc; Flood, Derek; Lepmets, Marion; Barry, Grainne
Abstract: Today, the growth of medical devices and mobile medical applications is increasing enormously, thanks to the efficiency and enhancement of new technology. When it comes to mobile medical apps, developers need to understand what is required when a mobile application fulfils the definition of a medical device. Such applications have to be developed in compliance with medical device regulations. This can be a challenge for mobile medical application developers, as medical device software is normally developed in a manner that will also ensure the production of regulatory documentation that is essential to market such devices. In this paper, we identify the need for a mobile medical application development framework, the key criteria for such a framework, and describe how the results were collected through performing a Medical Device Software Development workshop. Furthermore, we describe how MDevSPICE together with an agile software development approach can be tailored to support a mobile medical applications development framework. We detail one of the key criteria for mobile medical application development framework—traceability. Abstract : Mobile medical applications have to be developed in compliance with medical device regulations. These regulations require the production of regulatory documentation that is essential to market such apps. In this paper, we identify the need and key criteria for a mobile medical application development framework. Furthermore, we describe how MDevSPICE together with an agile development approach can be tailored to support a mobile medical applications development framework. Additionally, we detail a key criteria for mobile medical application development framework—traceability